Análise ergonômica da atividade do cultivo da macroalga Kappaphycus alvarezii na técnica de rede tubular na Baía da Ilha Grande - Medeiros, Guilherme Leonardo Soares (2020)
Algiculture, different from collection in natural stocks, involves the cultivation of algae in marine and coastal environments, and presents itself as an important alternative for the social improvement of coastal communities, through the generation of a source of income (GÓES, 2015). However, in the State of Rio de Janeiro, despite some initiatives and studies for the development of Kappaphycus alvarezii macroalgae crops, this type of activity is still incipient (CASTELAR, 2014). The tools and cultivation techniques used are adapted in order to meet the local coastal characteristics as a function of cultivation, necessary for the importance of studying the interaction of the social actor in this process, as well as for a potential ergonomic demand. In addition, there was a lack of data on ergonomics in this activity, affecting mainly populations of artisanal fishermen. In this sense, we intend to conduct studies of ergonomic analysis that aim to contribute to the health and quality of life of the worker, through the local case study, having as methodological tool the ergonomic analysis of this activity, considering the cultivation and management of algae in rafts and tubular nets, the participation of workers in this process being of great importance. For this, the OWAS tool was applied, in order to assist the classification of demands, plus the simulation through the CAD system (Computer Aided Design), which, in addition to the parametric study, allowed the creation of virtual prototypes and physical prototype of the tool insertion of algae in the tubular net. Studies show that, in some stages, workers are forced to adopt inappropriate postures and point to the need for processes. These results also enabled the development of a new study, still preliminary, of the design of a catamaran vessel to meet specifically the demands pointed out for this research. In support of all cultivation activities, design solutions with virtual prototypes and the physical prototype of the algae insertion tool in the tubular net, seem to have great potential for use in the Ilha Grande Bay region.